Pimobendan Improves Clinical Signs in Short Term Compared to Digoxin or Placebo in Dogs with Heart Failure Due to Chronic Degenerative Mitral Valve Disease - Maria Helena Matiko Akao Larsson (Acta Scientiae Veterinariae, 2014)
Background : Chronic degenerative mitral valve disease (CDMVD) continues to be the most common cause of heart failure (HF) in small breed dogs. Pimobendan (PIMO) is a mixed action drug with inotropic and vasodilator properties and is widely used to treat heart disease in dogs. Therefore, PIMO increases cardiac output, reduces both preload and afterload and increases myocardial contractility without increasing energy consumption and myocardial oxygen. Digoxin (DIG) is a cardiac glycoside acting through inhibition of the sarcolemmal Na+/K+ ATPase pump, hence increasing intracellular calcium. It exerts benefi cial effects on left ventricular function, symptoms and exercise tolerance. The purpose of this prospective, randomized, double blind clinical trial was to evaluate the clinical response and QoLQ in heart failure (HF) dogs treated with digoxin or pimobendan in addition to conventional therapy (furosemide and benazepril). Materials, Methods & Results : Inclusion criteria: dogs in class III or stabilized class IV (NYHA). Exclusion criteria: use of positive inotrope and antiarrhythmic, presence of atrial fi brillation, renal or hepatic disease or neoplasia. Thirty three dogs were included and randomly assigned to DIG (n = 11), PIMO (n = 14) and placebo (PL) (n = 8) and followed up weekly. Data was evaluated for days zero, 7, 14 and 28. Increasing score was assigned to each variable depending on worsening of clinical evaluation (history and physical exam, QoLQ and echocardiogram (echo).Three dogs died during treatment due to worsening of HF, one of PL group and two of DIG group; furthermore, one of PIMO group was censored due to worsening of heart failure. There was no signifi cant difference between and within groups for echo and radiography. PL and DIG groups did not show any signifi cant difference throughout the 28 days of treatment. PIMO group showed lower physical exam score and increased early mitral infl ow velocity on day 28. Serum creatinine increased on days 14 and 28 compared to baseline, but within normal limits. The groups were similar within each evaluation day. Discussion : This is the fi rst short term prospective randomized double blind study comparing PIMO to DIG or PL ad- ditionally to conventional therapy (ACEi and furosemide) for dogs with HF due to CDMVD. It was observed an early signifi cant clinical improvement in dogs receiving PIMO compared to those receiving DIG or PL. The increase in early mitral infl ow velocity (E-wave) on day 28 for PIMO group is suggestive of diastolic dysfunction improvement, but this is only one variable related to diastolic function. Creatinine concentration increased in PIMO group, although it remained within normal range. In the present study, although all the three groups received furosemide, only PIMO group showed increase in blood creatinine between baseline and days 7 and 28. This result must be explored in later studies. Regarding the exercise intolerance assessment in a QoLQ, it must be a